Three‐dimensional numerical simulations of methane gas migration from decommissioned hydrocarbon production wells into shallow aquifers. Issue 7 (31st July 2016) - Roy, N.; Molson, J.; Lemieux, J.‐M.; Van Stempvoort, D.; Nowamooz, A.
Abstract: Three‐dimensional numerical simulations are used to provide insight into the behavior of methane as it migrates from a leaky decommissioned hydrocarbon well into a shallow aquifer. The conceptual model includes gas‐phase migration from a leaky well, dissolution into groundwater, advective‐dispersive transport and biodegradation of the dissolved methane plume. Gas‐phase migration is simulated using the DuMu x multiphase simulator, while transport and fate of the dissolved phase is simulated using the BIONAPL/3D reactive transport model. Methane behavior is simulated for two conceptual models: first in a shallow confined aquifer containing a decommissioned leaky well based on a monitored field site near Lindbergh, Alberta, Canada, and secondly on a representative unconfined aquifer based loosely on the Borden, Ontario, field site. The simulations show that the Lindbergh site confined aquifer data are generally consistent with a 2 year methane leak of 2–20 m 3 /d, assuming anaerobic (sulfate‐reducing) methane oxidation and with maximum oxidation rates of 1 × 10 −5 to 1 × 10 −3 kg/m 3 /d. Under the highest oxidation rate, dissolved methane decreased from solubility (110 mg/L) to the threshold concentration of 10 mg/L within 5 years. In the unconfined case with the same leakage rate, including both aerobic and anaerobic methane oxidation, the methane plume was less extensive compared to the confined aquifer scenarios. Unconfined aquifers may therefore be less vulnerable to impacts from methane leaks along decommissioned wells. At other potential leakage sites, site‐specific data on the natural background geochemistry would be necessary to make reliable predictions on the fate of methane in groundwater. Key Points: Methane oxidation can be important in attenuating methane contamination from leaky wells in confined or unconfined aquifers Unconfined aquifers may be less vulnerable to methane contamination compared to confined aquifers Site‐specific background geochemistry (including oxygen and sulfate) should be monitored for determining impacts of dissolved methane